NEW DEVELOPMENTS IN RUSSIA-EU TRADE WITH AGRICULTURAL GOODS: INFLUENCES OF TRADE INTEGRATION - Erokhin Vasily; Anna Ivolga (Ekonomika Poljoprivrede (1979), 2013)
Trade of agricultural products in the last decades has become more and more globalized. The global trading system is now both freer and fairer than ever before, boosting global prosperity, making significant contribution to global economic development. Main goal of the paper is to analyze the current state of Russia-EU trade of agricultural products. The period of analysis includes 2001-2011. The analysis involved main exporting and importing countries for each analyzed product group. Sub-goals include an overview of the WTO threats and opportunities for Russian agriculture, and trade with agricultural products globally, as well as comparison of main consequences of WTO accession for such CIS countries as Kazakhstan, Ukraine, Kyrgyzstan, Georgia and Moldova. This is also, related to state support of agricultural production in Russia and CIS and its influence on volumes, directions, structure and effectiveness of international trade with agricultural products.